Risperidone and liver function tests in children and adolescents: A short-term prospective study - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Objective: Revealing of unknown adverse effects of atypical antipsychotics on pediatric population may take a long period of time. The purpose of this prospective study is to document changes in the liver function tests (LFTs) associated with risperidone usage in a group of children and adolescents. Method: Study subjects consist of 120 youths with ages ranging from 3-17 years. For this study, patients' baseline and follow-up weight and hepatobiliary function tests including alanine aminotransferases(ALT) and aspartat aminotransferases (AST), gamma gluatamyl transerase (GGT), alkaline phosphatase (ALP) and serum bilirubin levels were measured before and after the treatment period of one month. Results: Only one male patient's ALT levels increased up to three-fold and AST levels increased up to two-fold of the basal levels. First month mean levels of liver enzymes and billuribin of the patients were significantly higher than the baseline. Sixty-three patients (52.5%) showed an asymptomatic increase in the liver enzymes and/or billuribin levels of the first month of this study. Weight gain was observed in 58 patients (57.4%). There was no significant association between changes in weight and liver enzymes and billuribin levels. Conclusion: We found clinically non significant liver function test abnormalities mostly in the form of ALP elevation in 52.5% and marked liver enzymes elevation in 0.8% of risperidone-treated subjects. However use of concomitant medications and variations in age are the limitations of this study. These findings suggest that risperidone treatment in the short term may lead to liver function changes in children and adolescents. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: atypical antipsychotic; hepatotoxicity; liver enzymes; risperidone; side effects; PERVASIVE DEVELOPMENTAL DISORDER; DISRUPTIVE BEHAVIOR DISORDERS; ATYPICAL ANTIPSYCHOTIC-DRUGS; AGGRESSIVE YOUTH TRAAY; WEIGHT-GAIN; LONG-TERM; CHOLESTATIC HEPATITIS; ENZYME ELEVATIONS; TREATMENT RECOMMENDATIONS; INDUCED HEPATOTOXICITY